More than true the wisdom of fairy tales - Bly, Robert 1926-2021 (Henry Holt and Company, 2018)
"Few forms of storytelling have greater power to captivate the human mind than fairy tales, but where do these tales originate from, and what do they mean? Celebrated poet and bestselling author Robert Bly has been asking these questions throughout his career. Here Bly looks at six tales that have stood the test of time and have captivated the poet for decades, from "The Six Swans" to "The Frog Prince." Drawing on his own creative genius, and the work of a range of thinkers from Kirkegaard and Yeats to Freud and Jung, Bly turns these stories over in his mind to bring new meaning and illumination to these timeless tales. Along with illustrations of each story, the book features some of Bly's unpublished poetry, which peppers his lyric prose and offers a look inside the mind of an American master of letters in the twilight of his singular career"--
Keywords: Märchen; Fairy tales / History and criticism; Tales / History and criticism; Wisdom in literature; Truth in literature; Conduct of life in literature; Fairy tales / Psychological aspects; LITERARY COLLECTIONS / Essays; LITERARY CRITICISM / Fairy Tales, Folk Tales, Legends & Mythology; Fairy tales; Tales; Criticism, interpretation, etc